LUGARES DA QUALIRAGEM NA “ILHA DO AMOR”: DISSIDÊNCIAS LGBTQIAPN+ NO ESPAÇO URBANO DE SÃO LUÍS – MA - MARTINS, Ian Moura (2024)
The LGBTQIAPN+ population has historically been marginalized and rendered invisible in urban spaces. In view of this problem, this study aimed to analyze the scientific production of Brazilian Geography regarding the LGBTQIAPN+ population and the formation of the social movement represented by this acronym at the national, state, and local levels, as well as the most and least frequented places by these individuals in the dissenting urban space of São Luís - MA. To make this analysis operational, it was necessary to define a methodological path that initially sought the theoretical and methodological support necessary for the initial structuring of this work in the continuous and systematic literature review. As we read, we realized that Phenomenology was the method that best dialogued with the proposal of this research and as a key geographical category: place. These methodological approaches, together with qualitative and quantitative participant research, were essential for the construction and consolidation of data collection and the process of analyzing the results. Data collection involved documentary research and semi-structured interviews with 40 LGBTQIAPN+ individuals linked to the Federal University of Maranhão and leaders from LGBTQIAPN+ institutions. The interviews revealed the sociodemographic diversity of the interviewees, with the majority being young, low-income, and predominantly self-identifying as black or mixed-race. These characteristics directly influence the places they frequent or avoid in São Luís. As such, the Historic Center was view positively (topophilia), while heteronormative locations are avoided (topophobia). The analysis revealed that gender, race, class, culture, and religion markers are factors contributing to the construction of places of safety or fear. Considering this, encountering people with similar gender identity and sexual orientations promotes feelings of comfort and belonging not only in the Historic Center but also in other spaces or locations within the city. Additionally, discussions were held regarding the resistances and challenges faced by the LGBTQIAPN+ movement, such as institutionalized LGBTQIAPN+phobia and a lack of political engagement, especially among young people. Finally, the research aims to serve as a basis for future studies and the development of public policies that consider the diversity of the LGBTQIAPN+ population and their desires concerning leisure, security, and employability, emphasizing that the occupation of all urban spaces by the LGBTQIAPN+ population is crucial to combat LGBTQIAPN+phobia.